2022
DOI: 10.1186/s12967-022-03370-2
|View full text |Cite
|
Sign up to set email alerts
|

TPI1 activates the PI3K/AKT/mTOR signaling pathway to induce breast cancer progression by stabilizing CDCA5

Abstract: Background Triosephosphate isomerase 1 (TPI1), as a key glycolytic enzyme, is upregulated in multiple cancers. However, expression profile and regulatory mechanism of TPI1 in breast cancer (BRCA) remain mysterious. Methods Western blotting and immunohistochemistry (IHC) assays were used to investigate the expression of TPI1 in BRCA specimens and cell lines. TPI1 correlation with the clinicopathological characteristics and prognosis of 362 BRCA pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
4
28
0
Order By: Relevance
“…CDCA5 is aberrantly expressed in various types of cancer, such as hepatocellular carcinoma (35)(36)(37), bladder cancer (38), prostate cancer (39) and renal clear cell carcinoma (40), rendering it a potentially important prognostic marker and potential therapeutic target for cancer patients. However, only a limited number of studies (41)(42)(43) to date have investigated the expression and function of CDCA5 in BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…CDCA5 is aberrantly expressed in various types of cancer, such as hepatocellular carcinoma (35)(36)(37), bladder cancer (38), prostate cancer (39) and renal clear cell carcinoma (40), rendering it a potentially important prognostic marker and potential therapeutic target for cancer patients. However, only a limited number of studies (41)(42)(43) to date have investigated the expression and function of CDCA5 in BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the conclusion that it is loss of stability and lowered TPI levels ( affecting all TPI functions ) that underlie the disease and open up the possibility that loss of non-glycolytic functions of TPI may contribute to the disease, especially within the neuromuscular system. Indeed, several moonlighting roles have been identified, but the catalytic dependence of these roles is unknown (Daniel et al 2021 ; Jin et al 2022 ; Liu et al 2022 ; Rodriguez-Bolanos and Perez-Montfort 2019 ; Zhang et al 2021 ).…”
Section: Evidence For a Potential Non-catalytic Tpi Functionmentioning
confidence: 99%
“…In Zhang et al ( 2021 ), TPI was found to be regulated through an axis involving mTORC1 and cyclin-dependent kinase 2 (CDK2), where TPI phosphorylation by CDK2 at serine 80 (referred to as Ser117 in the paper referencing a predicted long TPI isoform) resulted in the translocation of TPI to the nucleus. Interestingly, another recent publication further highlighted the importance of mTORC1 in relation to TPI function, where it was shown that TPI promotes tumor growth and migration through an association with cell division cycle associated 5 (CDCA5) which led to the activation of phosphatidylinositol-3-kinase (PI3K) and subsequent activation of the protein kinase B (Akt/PKB) and mTORC1 pathways (Jin et al 2022 ). These two manuscripts suggest that TPI is both regulated by the mTORC1 pathway and that TPI can itself regulate the mTORC1 pathway, at least in cancer.…”
Section: Tpi Signaling Partnersmentioning
confidence: 99%
See 2 more Smart Citations